P055 London sexual health programme – developing innovative solutions to open access sexual health services. (14th July 2019) - Kelly, Adrian; Davies, Luke Byron; O'Sullivan, Jonathan; Clarke, Jan; Murchie, Martin; Kinsella, Ryan
Abstract : Background: Demand for sexual health services is increasing at a time when public funding has reduced. This Programme is a partnership of local government, working with England's National Health Service to improve access to sexual health services. A key part of our vision was to develop an online sexual health triage, home testing and treatment service, which work with a network of over 40 clinics. Methods: In order to achieve this, the Programme undertook widespread engagement across the city. This included a range of activities with service users, for example, online and clinic-based surveys and focus groups with underrepresented groups. Engagement also took place with clinicians, payorst and other stakeholders. Questions were asked to service users about their usage of services and the acceptability of new innovations, including online based self-sampling options. Clinical organisations were asked about the feasibility of online services being part of the clinical pathway. Alongside this engagement project, new governance arrangements, which took the form of legally binding agreements that enabled the parameters of a pan-London service procurement to take place. At the same time, payors agreed to align pricing for activity in clinics, to support system sustainability for both sides. Results: While many respondents said they value being able to go to a sexual health clinic, over half said they would use an online alternative.. With the governance for this partnership finalised: aligned service specifications for both clinic provision and an e-service, could take place for the online service which launched in January '18. The e-service has registered over 120k users since then Conclusion: The pressure of growing sexual health need on reduced public resource are self evident, doind more of the same was not a viable or sustainable option. With efficiencies brought about through citywide cooperation, robust clinical and commissioner governance structures, access to services in London has been enhanced. Disclosure: No significant relationships.